2010
DOI: 10.4103/0970-9371.66694
|View full text |Cite
|
Sign up to set email alerts
|

Significance of nuclear morphometry in cytological aspirates of breast masses

Abstract: Background:Breast carcinoma is the most common malignancy globally. Cytological evaluation in breast lesions is largely subjective. Gradual progression of cells from normal to invasive involves nuclear changes that need to be viewed objectively.Aims:This study aims to apply nuclear morphometry on cytological breast aspirates. It evaluates its utility in differentiating benign vs. malignant lesions and correlates it with cytologic grading in malignant cases.Setting and Design:Nuclear morphometric parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 9 publications
7
39
0
3
Order By: Relevance
“…while malignant ones had an MNA of 115.10±9.01 µm 2 , indicating a significant increase in MNA from the benign to malignant spectrum which is in concordance with studies done by Narasimha et al (6), Abdalla et al (7), and Kalhan et al (8). An intermediate MNA value of 107.03±6.60 was observed in borderline cases which is comparable to study by Narasimha et al (6) (Table III).…”
Section: Discussionsupporting
confidence: 82%
“…while malignant ones had an MNA of 115.10±9.01 µm 2 , indicating a significant increase in MNA from the benign to malignant spectrum which is in concordance with studies done by Narasimha et al (6), Abdalla et al (7), and Kalhan et al (8). An intermediate MNA value of 107.03±6.60 was observed in borderline cases which is comparable to study by Narasimha et al (6) (Table III).…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly the shape parameters did not help in the distinction (Abadalla et al, 2008). Kalhan et al showed that nuclear morphometry is a useful objective tool to differentiate between benign and malignant aspirates of breast lesions and also correlated significantly with cytologic grade (Kalhan et al, 2010). Mean nuclear area, long axis, short axis and total run length proved to be useful parameters in the study.…”
Section: 6919 Utility Of Nuclear Morphometry With Imagej In Effusionmentioning
confidence: 99%
“…The nucleus is the control center of cell, playing an important role in cell metabolism, growth and differentiation and is the major existing part of the genetic materials, and its pleomorphism alone could be used as the indicator of the possible aggressive or malignant behavior of tumors [12,13]. The nucleolus is the formation site of ribosomal predecessor, and within the cells with exuberant protein synthesis, the nucleoli would be plenty and big.…”
Section: Discussionmentioning
confidence: 99%